The crow [videorecording (DVD)] - Schow, David J.; Shirley, John, 1953-; Lee, Brandon; Hudson, Ernie; Wincott, Michael, 1958-; Davis, Rochelle, 1980-; Bai, Ling, 1966-; Shinas, Sofia; Kelly, David Patrick; Levine, Anna; Massee, Michael (Miramax/Dimension collector's series)
Exactly one year after a young rock guitarist and his fiancée are brutally murdered by a ruthless gang of criminals, he returns, watched over by a hypnotic crow, to seek revenge.